A study on phytogenotoxicity induced by biogenic amines: cadaverine and putrescine - Braga, Ana Paula Andrade [UNESP]; de Souza, Letícia Rosa [UNESP]; Lima, Maria Gabriela Franco [UNESP]; de Moraes Cunha Gonçalves, Matheus [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Springer Nature, 2024)
Among the compounds present in necro-leachate, a liquid released during the process of decomposition of the human body, are the biogenic amines cadaverine and putrescine. Although some studies on necro-leachate have indicated a potential ecotoxicological and public health risk associated with it, the research on this type of contamination is still rather limited. This study presents information about the phytotoxic and cytogenotoxic potential of cadaverine and putrescine, evaluated separately and within a mixture. Phytotoxicity was evaluated through a germination test, the initial growth of seedlings with Lactuca sativa, and cytogenotoxicity through chromosomal aberration and micronucleus tests with Allium cepa. The L. sativa results showed a phytotoxic effect for the evaluated amines, by reducing root (> 90%) and hypocotyl (> 80%) elongation. The co-exposure of cadaverine and putrescine potentiated cytogenotoxic activity by aneugenic action in the meristematic cells of A. cepa. From this result, it is possible to infer the eco-toxicogenic potential of cadaverine and putrescine. This study not only highlights the importance of the phytotoxic and cytogenotoxic effects of these amines but also emphasizes the urgent need for further investigation into contamination originating from cemetery environments. By evaluating the risks associated with necro-leachate, this research is aimed at informing global efforts to protect ecological and public health. Graphical Abstract: (Figure presented.)
Keywords: Allium cepa; Chromosomal aberrations; Lactuca sativa; Micronuclei; Necro-leachate; Root elongation